Student L1 use in culturally diver ESL classroom - Zhang, Yuhan (Journal of Education, Humanities and Social Sciences, 2025)
This paper discusses the role of students’ first language (L1) in culturally diverse ESL classrooms in the US. Drawing from personal experience and classroom observations, it critiques English hegemony and advocates for L1 inclusion to increase motivation, cultural identity, and language learning efficiency. Practical strategies like translanguaging and Culturally Responsive Teaching (CRT) are highlighted as ways to foster inclusivity and confidence in multilingual learners.